Relaciones Y Configuraciones Didácticas, Pedagógicas, Y Teóricas Que Forman Al Licenciado En Educación Física Y Deportes De La Universidad Del Quindío (2016)
This research work has been called "Relationships and educational settings, pedagogical, and theoretical forming the Bachelor of Physical Education and Sports University of Quindío. The goal is to identify the relations and educational, pedagogical, and theoretical configurations that form the Bachelor of Physical Education at the University of Quindío. The research approach was qualitative I implement nature and type micro ethnography. The population were students and teachers of the degree program in Physical Education and Sports of the University of Quindío and in-depth interview used as collection technique. From the findings and the reality investigated, you can answer the question about what are the relations and educational, pedagogical, and theoretical configurations training Degree in Physical Education and Sports of the University of Quindío where it was evident that these three aspects are interrelated in various ways, either among all as a starting point and an end point and with a close relationship between two aspects PEP. And PEF program of physical education and sports